Predicting the Date of Bud Burst in Grapevines - Swanepoel, J.J.; de Villiers, F.S.; Pouget, R. (South African Journal of Enology and Viticulture, 2017)
It was possible to forecast the date of bud burst under South African winter temperatures (Region III) using the Pouget-formulae and principles, and to establish a scale of bud burst for cultivars grown in South Africa. The sum of daily temperature effects was higher under the warmer South African conditions which resulted in changes in the formulae for determining the daily effect of temperature and the cultivar coefficient on the bud burst date. Highly significant linear relationships were, however, obtained and it was possible to predict the date of bud burst fairly accurately.